The speaker and communicative aids in the Maqamat of Badi al-Zaman al-Hamdhani - The Kufi Maqamat as an example - Alketbi, Alia Ali Saeed; Jaafar, Muhammad Hilmi Abdullah (Journal of Arabic Language Sciences and Literature, 2025)
This study aims to analyze the role of communication aids in constructing meaning in the Kufi Maqama, and to identify the types of aids used and how they interact with the linguistic and cultural context of the text. Communicative aids, such as pronouns, demonstrative pronouns, and circumstances of time and place, are essential tools in constructing literary texts because they help determine the references of discourse and guide the recipient's understanding. Through the analysis of the Kufi Maqama, it became clear that these aids play a crucial role in constructing characters, developing events, and deepening the narrative experience. These aids also help in understanding the relationship between the speaker and the addressee and the cultural context in which the text was produced. The study concluded that the use of communicative aids in the Kufi Maqama distinguishes it from other texts and reflects the writer's skill in employing language to serve his artistic goals. The study recommended the need to deepen the study of communicative aids and conduct in-depth research in various textual genres to explore their role in literary and poetic communication, and to include the study of communicative aids in Arabic language curricula to stimulate critical understanding of texts, and to expand the study of Maqama by clarifying the role of communicative aids in other Maqama by Badi' al-Zaman al-Hamadhani and other writers, and to develop digital tools that help in analyzing communicative aids automatically within literary and communicative texts.
Keywords: Badi' al-Zaman al-Hamadhani; circumstances of time and place; Communicative aids; contextual aids; demonstrative pronouns; Kufi Maqama; personal aids; pronouns; speaker